Horticulture land: guide to being a plantsman through green game / Nurul Athirah Umairah Mohd Nizam … [et al.] - Mohd Nizam, Nurul Athirah Umairah; Mat Zain, Nurul Hidayah; Abdul Aziz, Azlan; Johari, Siti Nuramalina; Mohd Yasin, Anita (Faculty of Computer and Mathematical Sciences, 2023)
Planting and nurturing trees and plants as a part of horticulture is known as gardening. In today's tight economy, some people begin gardening to save money. Growing a garden can reduce expenses on groceries as it yields homegrown vegetables and fruits. However, limited gardening knowledge was the main barrier that stopped people from gardening. In addition, the traditional method of learning gardening fails to cultivate a sense of enjoyment and leads to discomfort, distraction, and disengagement. Therefore, we developed a Horticulture Land game that allows users to learn about gardening in risk-free and enjoyable ways by providing virtual gardening activities. The game follows the Game Development Life Cycle (GDLC) methodology, ensuring a systematic and effective development process. The development of Horticulture Land is based on the EGameFlow Model consists of seven elements: Concentration, Goal Clarity, Feedback, Challenge, Autonomy, Immersion, and Knowledge Improvement. In conclusion, Horticulture Land offers a unique opportunity to foster a deep and meaningful connection with the natural world. It challenges the perception of gaming as a solitary and sedentary activity by encouraging players to explore, learn and enjoy in a digital ecosystem.